Influence of Heat Treatment Temperature on Phase Transformation Behaviour and Mechanical Performance of Ti50Ni39Zr10Nb1 SMA - Ibrahim, Pshdar Ahmed; Baiz, Sivar Aziz; Mohammed, Safar Saeed; Balci, Esra; Dağdelen, Fethi (İstanbul Üniversitesi, 2026)
[Abstract Not Available]
Keywords: Güvenilir Sistemler